PENGELOLAAN KESAN KYAI GUS BAHA SEBAGAI MAKNA PANGGUNG DEPAN DAN PANGGUNG BELAKANG DALAM PENYIARAN DAKWAH ISLAM - Firdaus Yuni Dharta; Iswahyu Pranawukir; Mohamad Sudi; Gracia Rachmi Adiarsi; Yanti Setianti (Busyro: Jurnal Dakwah dan Komunikasi Islam, 2024)
This research employs Erving Goffman's dramaturgical theory, which divides social life into front stage and backstage, to analyze the management of Kyai Gus Baha's broadcasts in Islamic preaching. Utilizing a qualitative approach and literature review method, the study examines 50 sermons by Kyai Gus Baha, audience comments, and interviews with individuals close to him. The findings reveal that Kyai Gus Baha uses friendly and easily understandable language in 90% of cases, controlled humor in 60%, references to the Quran and Hadith in 100%, and messages of peace and tolerance in 80% of instances. Additionally, he discusses everyday life in a friendly manner in 70% of cases. Audience reactions indicate appreciation for intelligence and depth of knowledge (40%), kindness and gentleness (30%), humor and emotional connection (20%), and relevance to daily life (10%). Interviews disclose that Kyai Gus Baha's personal life is simple, honest, and aligned with his teachings, acknowledged by respondents (80-100%). In conclusion, Kyai Gus Baha effectively and consistently manages presentations between the front and backstage, thereby enhancing the credibility and effectiveness of his sermons. This study underscores the importance of alignment between teaching and actions in building credibility in Islamic preaching.